Effectiveness of Fulfilling the Basic Needs of Communities in the Border Area in Nunukan District, North Kalimantan Province - Hidayat, Taufik; Ibrahim, Muh. Akmal; Sukri, Sukri; Yunus, Muhammad (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Development in the trade sector is an effort or strategic step in development in the border area, one of which is fulfilling the basic needs of the border community in Nunukan Regency, North Kalimantan Province. This study aims to analyze the effectiveness of fulfilling the basic needs of the border community in Nunukan Regency, North Kalimantan Province. This study uses a qualitative approach with data collection methods, namely observation, interviews, and documentation. Data sources consist of primary and secondary data. The data analysis technique used is an interactive analysis model. The informants in this study are parties who are authorized and directly involved in meeting the basic needs of the border area in Nunukan Regency, North Kalimantan Province. The results of the study indicate that the effectiveness in fulfilling the basic needs of border communities in Nunukan Regency, North Kalimantan Province is not yet effective enough. This is because in fulfilling basic needs in the border area, there is no set target. There are no regulations in this case, regional regulations and their derivatives that regulate the fulfillment of basic needs, especially the Transportation Cost Subsidy (SOA). The basis of the Transportation Cost Subsidy (SOA) policy has not been stated in regional regulations and has not been stated in the Governor's regulation. With the limited resources owned by the local government, it cannot accommodate all border area routes in Nunukan Regency, North Kalimantan Province, so the local government chooses and prioritizes the route or route of the Goods Subsidy Program (SOA) in sub-districts that have more demand and needs and are most in need.